Evaluation of the Aesthetic and Social Function of the Bendosari Park Salatiga City - Roynaldo Kristi; Dr.Ir. Bistok Hasiholan Simanjuntak M.Si (Indonesian Journal of Computing and Modeling, 2018)
To function improve from the Bendosari park value, aesthetic and social function evaluation must be conducted. This study aims to evaluate the landscape characteristics of Bendosari Park based on aspects of the aesthetic and social function. The research was conducted in Bendosari Park on Ring Road of Salatiga City, Central Java Province, Indonesia from June until August 2017. Evaluation of the aesthetic and social function used close questionnaire method toward 30 respondents with respondents criteria of aged over 12 years and analyzed using KPI (Key Performance Indicator) method to find out how far the two aspects (the aesthetic and social) are reached. The study indicates that Bendosari Park has fulfilled the social and aesthetic functions of the park which indicated by the value of KPI analysis greater than 0.67.